Transformación genética del arroz - Tabares Z., Eddie (International Center for Tropical Agriculture, 2010)
Genetic transformation in rice Among monocotyledons, rice is the first cultivated species to undergo genetic transformation and regeneration. Rice cultivars of the japonica group were the first to be transformed, followed by numerous javanica and indica cultivars, which were regenerated as fertile plants. Most rice transformation studies have used direct DNA transfer in protoplasts, induced by different post-treatments. Other transformation methods less dependent on the genotype have been recently developed, including biolistic transformation and use of Agrobacterium tumefaciens. Both use rice plant explants, such as inflorescences and mature and immature embryos.